Correction: An overview of metamaterials and their achievements in wireless power transfer. Issue 15 (9th April 2018) - Sun, Kai; Fan, Runhua; Zhang, Xihua; Zhang, Zidong; Shi, Zhicheng; Wang, Ning; Xie, Peitao; Wang, Zhongyang; Fan, Guohua; Liu, Hu; Liu, Chuntai; Li, Tingxi; et al.
Abstract : Correction for 'An overview of metamaterials and their achievements in wireless power transfer' by Kai Sun et al., J. Mater. Chem. C, 2018, DOI: ; 10.1039/c7tc03384b .